The Role of Optical Coherence Tomography in Diagnosis and Grading of Papilledema and its Correlation to Clinical Assessment - Estefan, Marina; Asaad, Keroles Farah (British Journal of Healthcare and Medical Research, 2025)
Background: Papilledema, or optic disc swelling because of elevated intracranialpressure, was sorted using the Frisen Scaling. Optical coherence tomography (OCT) is a possible device to measure variations in the degrees of papilledema and to displaythe effectiveness of treatments. Objective: To identify and correlate the role of the OCT of the optic nerve head with the clinical grading of papilledema using the Frisen Scale via digital fundus photographs. Patients and methods: This was a randomized trial in which 50 eyes with papilledema have been enrolled from the cases attending the outpatient clinic of Beni-Suef University Hospital. Digital optical disc photos of the left or right eye have beenchosen for comparison with OCT optic nerve head (ONH) images results. To correlate OCT results with clinical grading of papilledema using the Frisen scale. Results: There was a highly significant association between stages of papilledema by OCT and stages of papilledema by modified Frisen scale (p.value<0.001). A strong positive significant association among stages of papilledema by OCT and stages of papilledema by modified Frisen scale (r= 0.871, P <0.001). Conclusion: Present OCT measurements may be beneficial as an adjunct to clinical grading. For lower-stage anomalies, OCT compares positively with clinical grading of optic nerve photos. With elevated stages, OCT-RNFLT processing algorithms frequently failed.